1961
DOI: 10.1002/cber.19610941003
|View full text |Cite
|
Sign up to set email alerts
|

Eine Methode zur Identifizierung von aus unsymmetrischen β‐Diketonen und Hydrazinderivaten erhältlichen Pyrazolderivaten

Abstract: Die beiden isomeren Pyrazolderivate II und III werden durch Umsetzen schwach saurer 2.4‐Dinitrophenylhydrazin‐Lösungen mit dem exo‐Enolester des 2‐Acyl‐cycloalkanons bzw. mit dem 2‐Acyl‐1‐morpholino‐cycloalken und nachfolgendes Erwärmen mit Säure erhalten. Freies 2‐Acetyl‐cyclopentanon und‐hexanon reagieren mit 2.4‐Dinitrophenylhydrazin primär an der exo‐Carbonylgruppe unter Bildung des Pyrazolderivats III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1963
1963
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The yields, physical properties and analytical data of the previously unreported compounds are given in Table 6. The following compounds have been previously reported but their isomeric distributions were not reported: 1-pyrrolidino-2(or 5)-acetylcyclopentene (2a) [26]; 1-morpholino-2(or 5)-acetylcyclopentene (2c) [4] 1-(3-azabicyclo[3.2.2]nonylamino-2(or 5)-methylcyclohexene (1f) [27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The yields, physical properties and analytical data of the previously unreported compounds are given in Table 6. The following compounds have been previously reported but their isomeric distributions were not reported: 1-pyrrolidino-2(or 5)-acetylcyclopentene (2a) [26]; 1-morpholino-2(or 5)-acetylcyclopentene (2c) [4] 1-(3-azabicyclo[3.2.2]nonylamino-2(or 5)-methylcyclohexene (1f) [27].…”
Section: Methodsmentioning
confidence: 99%
“…( We produced cyclohexenyl enamines with acetyl substituents in the 2-and 6-positions and cyclopentenyl enamines with acetyl substituents in the 2-and 5-positions in two different ways. They were synthesized by direct carbon acylation of the enamine [3,4] and by reaction of an acetylcycloalkanone with a secondary amine [5,6] (Scheme 1). We have found that the isomeric distributions of enaminoketones 1 and 2 are essentially the same for each of the two alternative methods of synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Saturated bicyclic pyrazoles are typically prepared by the Knorr condensation of a hydrazine derivative with a 1,3-dicarbonyl compound , (Scheme a) or an equivalent substrate. , Alternative procedures involve variations of the 1,3-dipolar cycloaddition (Scheme b). − , The main drawback of these methods lies in the often laborious preparation of the required starting materials, which can limit the available functionality in the product and precludes the late-stage introduction of structural diversity. In addition, some saturated heterocyclic systems have been noted to give unexpected rearrangement products under Knorr condensation conditions …”
Section: Introductionmentioning
confidence: 99%